Statement by the Kommission OVAR of the AGO Study Group on the Use of HIPEC (Hyperthermic Intraperitoneal Chemotherapy) to Treat Primary and Recurrent Ovarian Cancer - Harter, P.; Mahner, S.; Hilpert, F.; Runnebaum, I.; Ortmann, O.; Mustea, A.; Sehouli, J.; du Bois, A.; Wagner, U.; null (Geburtshilfe und Frauenheilkunde, 2013)
HIPEC is offered to patients with ovarian, fallopian tube or primary peritoneal cancer at some hospitals. Altogether, there is still no evidence that HIPEC leads to an improvement of prognosis in any gynecologic tumor, neither in primary therapy nor in treatment of relapse. The available data indicate an increased complication rate which might negatively impact the benefit-risk balance of this procedure. In addition, standard treatment with proven efficacy might be withheld due to application of unproven methods. The use of HIPEC outside of well designed, prospective and controlled clinical trials is therefore disregarded.
Keywords: ovarian cancer; statement; HIPEC; AGO